The Utilization of Tamarind Seeds (Tamarindus indica L.) as the Natural Coagulant for Wastewater Treatment of Traditional Gold Mine: Penggunaan Biji Asam Jawa (Tamarindus indica L.) sebagai Koagulan Alami pada Pengolahan Limbah Cair Tambang Emas Tradisional - Hidayah, Rofi’ul; Effendi, Hefni; Hariyadi, Sigid (Habitus Aquatica, 2022)
Tamarind seeds (Tamarindus indica L.) are seeds that contain proteins, tannins, and antioxidants that can be used as a natural coagulant in wastewater treatment, including wastewater of traditional gold mine. The method used in the study was coagulation with a speed of 200 rpm for one minute and 20 rpm for 30 minutes. The purpose of the study is to determine of tamarind seeds powder dose for wastewater treatment of traditional gold mine. The present study used different dosages of tamarind seeds powder (0.3 g/L; 0.4 g/L; and 0.5 g/L) with three replications. The results of the study are changes in water quality parameter values of the initial conditions of wastewater. The decrease between the control field (KL) with increasing doses indicated by parameter in 0.4 g/L was TSS (96.95%), 0.3 g/L was COD (76.74%), and 0.3 g/L was mercury (93.03%). pH tend to increase in the experiments, for 0.3 g/L treatment the COD increase up to 44.79%. The best treatment dose of coagulant seeds powder acids that can be used in wastewater of traditional gold mine is a dose of 0.3 g/L.